2018
DOI: 10.1111/cen3.12438
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated T cells in multiple sclerosis

Abstract: Multiple exogenous signals received from cell surface molecules or cytokines play a significant role in altering the host immune response. In chronic autoimmune-mediated diseases, such as multiple sclerosis (MS), immune cells, especially T cells, are involved in the long-term pathophysiology. In the past few decades, mechanisms of pathogenic T-cell involvement at the onset or relapse of disease have been highlighted. However, the factors controlling the disease course have yet to be elucidated because of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 87 publications
(152 reference statements)
0
17
0
Order By: Relevance
“…The current understanding of the pathogenesis includes the peripheral activation of myelin-reactive effector CD4 T helper (TH) 1 cells, memory B cells and TH17 cells. [1][2][3] Furthermore, there is emerging evidence for a key role of TH17.1 cells, which share inflammatory features of TH17 and TH1 cells. 4,5 Cladribine (CLAD, MAVENCLAD â ) is an oral drug approved for treatment of active relapsing-remitting MS. 6 This synthetic deoxyadenosine analogue is a prodrug, which selectively depletes immune cells by apoptosis through the caspase system.…”
Section: Introductionmentioning
confidence: 99%
“…The current understanding of the pathogenesis includes the peripheral activation of myelin-reactive effector CD4 T helper (TH) 1 cells, memory B cells and TH17 cells. [1][2][3] Furthermore, there is emerging evidence for a key role of TH17.1 cells, which share inflammatory features of TH17 and TH1 cells. 4,5 Cladribine (CLAD, MAVENCLAD â ) is an oral drug approved for treatment of active relapsing-remitting MS. 6 This synthetic deoxyadenosine analogue is a prodrug, which selectively depletes immune cells by apoptosis through the caspase system.…”
Section: Introductionmentioning
confidence: 99%
“…We identified dSNPs in the SHMT1 gene, a published MS GWAS locus [14], where DeepWAS QTL network analysis pinpoints the TF Ying Yang 1 (YY1), expressed in multiple cell lines including immune related cells, as a potential novel risk factor (S3 Fig). YY1 is a ubiquitously expressed TF shown to be essential for B cell development [42] and serves as master regulator of T cell exhaustion [43]. Such dysregulation of immune related cells has been shown to promote MS progression [44]. Additional SNP-protein association studies (pQTLs) [45] that showed how the dSNP rs2273030 alters YY1 protein abundances could be extended to develop clinical applications in the context of MS.…”
Section: Discussionmentioning
confidence: 99%
“…YY1 is a ubiquitously expressed TF shown to be essential for B cell development 62 and serves as master regulator of T cell exhaustion 63 . Such dysregulation of immune related cells has been shown to promote MS progression 64,65 . Additional SNP-protein association studies (pQTLs) 66 that show how the deepSNP rs2273030 alter YY1 protein abundances could be extended to develop clinical applications in the context of MS.…”
Section: Discussionmentioning
confidence: 99%